Evaluation of genetic diversity of Katingan catlle and their genetic relationship with some other local catlle through DNA microsatellite analysis - Bambang Ngaji Utomo; R.R. Noor; c. Sumantri; I Supriatna; E.D. Gurnadi (Indonesian Center for Animal Research and Development (ICARD), 2011)
Katingan cattle is one of Indonesian animal genetic resources located in Katingan District, Central Kalimantan. The Katingan cattle is predicted to be extint, therefore it is necessary to conserve the cattle. Breed characterization is the primary step in any conservation program. Characterization was done using 10 microsatellite markers to evaluate the genetic diversity of Katingan Cattle in three subpopulations and their genetic relationship with some other local cattle. A total number of 72 random whole blood of Katingan samples consisted of Pendahara (20 samples), Buntut Bali (20 samples), and Tumbang Lahang (32 samples) were used. The samples of Bali, PO, and Limousine Cattle were 11, 6, and 3 respectivelly. The number of 136 aleles were found with the variation from 9 aleles (ILSTS089) to 18 aleles (ILSTS013) and the average of the alele was 13.6 aleles per locus. A number of alel from Tumbang Lahang was higher (10.8 aleles) than Pendahara (10.4 aleles) and Buntut Bali subpopulation (7.3 aleles). Some loci produced polymorphic diagnostic aleles which varied from 1-7 types of allele. HEL013 and BM1818 had four aleles, while ILSTS026 and ILSTS089 had five and six aleles respectively. ILSTS029 and ILSTS036 had seven aleles. The diagnostic aleles were also found in Tumbang Lahang subpopulastion, as well as in Pendahara, and Buntut Bali. Heterozigositas values of Pendahara, Buntut Bali, and Tumbang Lahang subpopulation were 0.454, 0.478, and 0.529 respectively. While the average of heterozigositas (Ĥ) was 0.492. Subpopulation of Tumbang Lahang was closer genetically to Pendahara (0.169) than Buntut Bali (0.173) and also the subpopulation was closer genetically to PO cattle (0.259) when compared to Buntut Bali (0.311) and Pendahara (0.329). The population of Katingan cattle was within one kluster with PO Cattle. Key Words: Katingan Cattle, Microsatellite, Genetic Diversity